Turkmen Marriage in The City of Erbil: Anthropological Study - Rashad Sabre Meran; Nadia Wali Jabbar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Marriage is a social ritual and a cultural component, as it performs a cultural function among the Turkmens in the city of Erbil. The main question is: How does the marriage ceremony go between the Turkmen in the city of Erbil? What change has happened to this ceremony? What are the types of marriage for the Turkmen in the city of Erbil? What is the extent of their commitment to these ceremonies? The main objective is: shed light on marriage as a transit ritual and analyze the meanings and stages that marriage goes through among the Turkmen, as well as analyzing the meanings and ceremonies of: Mawlid, Aglanja, Essoubiah, and henna among the Turkmens in the city of Erbil. Marriage ceremonies are generally held in the following order: finding and acquaintance with the bride, asking for her hand, betrothal, contracting the marriage contract, preparing the wedding requirements, henna, wedding day party, weekly, and other things. Study methods: (ethnographic) and (descriptive-analytical). Research community all of the Turkmen living in the city of Erbil. The study sample is the purposive sample of the snowball type. Tools Information collection (interview, observation, participatory observation). (12) Turkmen people living in the city of Erbil were interviewed, (2) of them were men and (10) of them were women. Among the results of the study, marriage is a sacred process of great importance, and that detailed measures are being held for it among the Turkmens in the city of Erbil. Marriage when Turkmen is often an external marriage. The stages of marriage for the Turkmen have their own social duties and have specific symbols and meanings that reflect the social foundations of that nationalism. Each stage of marriage includes a specific social function through which they try to protect their traditions and entity and exercise social control over their group.